SCIENCE REVIEW MATERIALS (Sci-ReMs) FOR GRADE 3 LEARNERS - Anna Marie L. Abes; Andrian A. Dela Cruz (International Journal of Educational Excellence and Innovation, 2024)
This study presents the development and validation of a Science Review Materials (Sci-ReMs) aimed at equipping and preparing Grade 3 learners with essential skills and competencies in the different branches of science namely matter; living things and their environment; force, motion and energy; and earth and space for successful examination experiences. Employing a descriptive research design using Research and Development (R&D) methodology, the level of mastery of the learners from eight elementary schools classified as last mile schools in the Schools Division of Ilocos Norte was described. Likewise, the level of validity of the developed Sci-ReMs was described using mean. Five science experts were tapped to validate the Sci-ReMs using the DepEd Evaluation Rating Sheet for Print Resources. Findings indicate significant deficiencies in learners' understanding across science disciplines, particularly in matter classification, living things and their environment concepts, force, motion and energy principles, and earth and space phenomena. Consequently, the development of Sci-ReMs emerged as a crucial intervention measure, rated valid across content, format, presentation, organization, accuracy, and up-to-datedness. The study concludes that Grade 3 learners require targeted interventions to bolster scientific skills for successful test outcomes, with Sci-ReMs standing as a valid tool for this purpose. The Sci-ReMs are aligned with Instructional Scaffolding Theory, bridging cognitive gaps through structured assistance, and scaffolding strategies, offering step-by-step guidance to enhance scientific proficiency and confidence. Thus, Sci-ReMs may serve as a scaffold for science learning, providing tailored support to address unmastered competencies and potentially improve examination performance.